2019
DOI: 10.1038/s41598-019-42435-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural bases of peptidoglycan recognition by lysostaphin SH3b domain

Abstract: Staphylococcus simulans lysostaphin cleaves pentaglycine cross-bridges between stem peptides in the peptidoglycan of susceptible staphylococci, including S. aureus . This enzyme consists of an N-terminal catalytic domain and a cell wall binding domain (SH3b), which anchors the protein to peptidoglycan. Although structures of SH3bs from lysostaphin are available, the binding modes of peptidoglycan to these domains are still unclear. We have solved the crystal structure of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 58 publications
(69 reference statements)
3
65
0
Order By: Relevance
“…a, G5 peptide; b, P4; c, P4-G5; d, P5-G5-P4; f, GM-P5-G5-GM-P4-G5. Titrations confirmed the existence of a narrow cleft previously proposed to bind the PG crossbridges 19 and recently shown to interact with pentaglycine 20 . They also revealed a set of residues interacting with the peptide stem, located on the face of the protein opposite to the G5 binding cleft.…”
Section: Figure 1 Mapping the Interaction Surface Of The Sh3b Domainsupporting
confidence: 76%
See 2 more Smart Citations
“…a, G5 peptide; b, P4; c, P4-G5; d, P5-G5-P4; f, GM-P5-G5-GM-P4-G5. Titrations confirmed the existence of a narrow cleft previously proposed to bind the PG crossbridges 19 and recently shown to interact with pentaglycine 20 . They also revealed a set of residues interacting with the peptide stem, located on the face of the protein opposite to the G5 binding cleft.…”
Section: Figure 1 Mapping the Interaction Surface Of The Sh3b Domainsupporting
confidence: 76%
“…The specificity of lysostaphin towards staphylococci has been attributed to its binding domain, which recognizes pentaglycine crossbridges 18,19 . Recent crystallographic studies have confirmed early models and showed that the pentaglycine stem is recognized by a shallow groove formed between strands β1-β2 and the RT loop, the binding specificity being essentially conferred by steric hindrance 20 . Despite this exquisite recognition mechanism, the SH3b domain displays a very weak affinity for the pentaglycine stems and binding has been shown to be optimal with multimeric peptidoglycan fragments, suggesting a mechanism more complex than initially anticipated 20,21 .…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Lysostaphin has an SH3b cell wallbinding domain that recognizes the pentaglycine cross-bridges present exclusively in staphylococcal peptidoglycan, positioning the enzyme to cleave the cross-bridges. Within the SH3b domain resides a shallow groove that appears to sterically select for pentaglycine (112). Just this year, Gonzalez-Delgado et al (110) discovered that the SH3b domain drives not only the specificity, but also high-affinity binding, of lysostaphin toward staphylococcal peptidoglycan.…”
Section: Connecting Cell Wall Biochemistry With Biological Functionmentioning
confidence: 99%
“…Other authors also reported a binding spectrum at the genus level for other CBDs from Staphylococcus endolysins 39,52,56 . Some studies suggested that CBDs recognize conserved binding ligands such as the glycine-rich inter-peptide bridge common to most staphylococcal strains [57][58][59] , as it has been reported for the SH3b-like cell wall targeting domain of lysostaphin 60 , which can explain their broad host range. Curiously, the GFP-AMI_SH3 protein demonstrated some binding affinity to two Enterococcus strains and one S. pneumoniae strain.…”
Section: Discussionmentioning
confidence: 86%